Autophagosome Requires Specific Early Sec Proteins for Its Formation and NSF/SNARE for Vacuolar Fusion - Ishihara, Naotada (The American Society for Cell Biology, 2001)
Double membrane structure, autophagosome, is formed de novo in the process of autophagy in the yeast Saccharomyces cerevisiae, and many Apg proteins participate in this process. To further understand autophagy, we analyzed the involvement of factors engaged in the secretory pathway. First, we showed that Sec18p (N-ethylmaleimide-sensitive fusion protein, NSF) and Vti1p (soluble N-ethylmaleimide-sensitive fusion protein attachment protein, SNARE), and soluble N-ethylmaleimide-sensitive fusion protein receptor are required for fusion of the autophagosome to the vacuole but are not involved in autophagosome formation. Second, Sec12p was shown to be essential for autophagy but not for the cytoplasm to vacuole-targeting (Cvt) (pathway, which shares mostly the same machinery with autophagy. Subcellular fractionation and electron microscopic analyses showed that Cvt vesicles, but not autophagosomes, can be formed in sec12 cells. Three other coatmer protein (COPII) mutants, sec16, sec23, and sec24, were also defective in autophagy. The blockage of autophagy in these mutants was not dependent on transport from endoplasmic reticulum-to-Golgi, because mutations in two other COPII genes, SEC13 and SEC31, did not affect autophagy. These results demonstrate the requirement for subgroup of COPII proteins in autophagy. This evidence demonstrating the involvement of Sec proteins in the mechanism of autophagosome formation is crucial for understanding membrane flow during the process.